Domination numbers of cardinal products of graphs : dissertation - Klobučar, Antoaneta (A. Klobučar, 1997)
Summary: In this work the explicit formulas for the domination numbers of the cardinal products of two paths and twocycles are given. Beside this it has been examined when Vizing's conjecture holds, in other words when for two graphs G and H [gama](G*H=[gama](G).[gama](H) holds. The limits lim and lim are given, too. At the end of the work the k-domination is treated, as a generalized term of domination, as well as explicit formulas for k-domination numbers of cardinal products two paths and two cycles.